Peningkatan Hasil Belajar Peserta Didik dalam Pembelajaran Geometri Materi Ciri, Komposisi dan Dekomposisi Bangun Datar Menggunakan Model Problem Based Learning (PBL) di Kelas IV SDN 07 Simpuruik Kabupaten Tanah Datar - Syarif, Anita; Ahmad, Syafri (Asian Journal of Early Childhood and Elementary Education, 2025)
This study was motivated by the low learning outcomes of students caused by the lack of learning activities that involve students. The purpose of this study was to describe the improvement of students' learning outcomes in learning Geometry material Characteristics, Composition, and Decomposition of Flat Buildings using the Problem Based Learning (PBL) model in class IV SDN 07 Simpuruik Tanah Datar Regency. This type of research is classroom action research (PTK) with qualitative and quantitative approaches. The research was conducted in two cycles, which consisted of planning, implementation, observation, and reflection. The data obtained relates to learning outcomes using the Problem Based Learning model, with data collection techniques in the form of tests and non-tests. The subjects of this study included the class teacher as an observer, the researcher as a practitioner, and class IV students totaling 20 people. The results showed that: First, the teaching module in cycle I obtained an average of 85.4% (B), increasing in cycle II to 95.8% (SB). Second, the results of the implementation of teacher aspect learning in cycle I averaged 82.14% (B), increasing in cycle II to 96.42% (SB). Third, the results of the implementation of learning aspects of students in cycle I averaged 78.56% (B), increasing in cycle II to 92.85% (SB). Fourth, the learning outcomes of students in cycle I averaged 71.84% (C), increasing in cycle II to 87.5% (B). Thus, it can be concluded that the Problem Based Learning (PBL) model is effective in improving student learning outcomes in Geometry learning in class IV SDN 07 Simpuruik Tanah Datar Regency.